Dynamic modelling of a ground-coupled solar ejector cooling system. Issue 11 (1st December 2022) - Mazloum, Youssef; Ghanem, Akram
ABSTRACT: This work presents a solar-driven air conditioning system based on ejector technology with closed-loop vertical geothermal boreholes. Modeling and simulation are carried out using Dymola software for dynamic transient analysis, with the refrigerant R134a. Condenser temperature regulation produces a 267% improvement of performance compared to a solar-only configuration. Solar fraction increases with increasing solar collector area, which benefits the system up to the limit of 27 m 2 for a cooling load of 9 kW. The reservoir volume ensuring high solar fraction is 14 m 3 . Optimal generator saturation temperature ensures a seasonal coefficient of performance value of 0.772 and a maximum overall efficiency of 39%. When the system encounters deviations from the optimum set point, the overall efficiency becomes 37.4%.